Social impact projections for Qatar youth residents from 2022: The case of the IAAF 2019 - Ishac, Wadih; Swart, Kamilla (Frontiers in Sports and Active Living, 2022)
While sport is playing an increasingly important role in society in the Middle East, there has been limited research on the perceived social impact of the hosting of major international events in this region. This study evaluates the main factors affecting youth residents’ perceptions of hosting major international sport events, by measuring the psychic income in particular, generated within subgroups shaping their support towards hosting these events. Pyschic income refers to the emotional and psychological benefit residents perceive they receive from hosting an international sport event. The study is of significance within the context of residents’ perceptions studies given that the large majority of residents in Qatar are non-Qataris. Furthermore, the youth were the target population for this study given that they have been identified as the custodians of the next generation and as an essential force in moulding national development; and extends the few residents’ perception studies in Qatar which comprised the general population. Using the 2019 IAAF Athletics World Championships as an example, a framework by Kim and Walker was adopted. Data were collected from 316 university students’ from different nationalities residing in Qatar; a month after the event took place. After conducting confirmatory factor analysis, this study was subject to structural equation modeling. Overall, the results show that the perceived impact on Qatari youth nationals was higher compared to Arab youth, and non-Arab youth, respectively. Likewise, the perceived impact was higher for females compared to males. By evaluating the psychic income received by youth from different nationalities residing in Qatar, this study provides decision-makers and organisers with a better understanding of the outcome generated from hosting major international sport events, and how they can leverage these going forward. Of importance is that even if youth residents do not attend the event in person, these events may still generate positive psychic income which is particular relevant to the 2022 FIFA World Cup given the limitations related to purchasing tickets. With Qatar establishing itself as a regional sport hub by attracting a diverse range of international sport events, a cumulative approach to understanding psychic income is recommended.